Tasmannia lanceolata leaf extract alleviates stretch mark appearance in a randomized, placebo‐controlled clinical trial in women and stimulates extracellular matrix synthesis in ex vivo human skin explants. (31st October 2020) - Gaillard, Emmanuelle; Boisnic, Sylvie; Branchet, Marie‐Christine; Lamour, Irène; Keophiphath, Mayoura
Abstract: Background: The leaves of Tasmannia lanceolata mainly contain polygodial that is known to exhibit a range of biological functions including anti‐inflammatory effects. Aims: These studies aimed to assess the effects of Tasmannia lanceolata extract (TLE) on skin and more particularly on stretch marks in women. Patients/Methods: A double‐blind, randomized, placebo‐controlled clinical study was carried out on 29 women, aged from 25 to 60 years, to investigate the effects of TLE on stabilized stretch marks. TLE and placebo products were topically applied daily for 8 weeks. Skin roughness and firmness of stretch marks were assessed by 2D and 3D photograph processing and analyses. Dermal density and thickness were evaluated using ultrasound, while stretch mark conditions (length, color, and depth) were determined by clinical scoring. Matricial proteins (pro‐collagen I and elastin) and pro‐matricial factors, like TGF‐β concentrations, were quantified from cultures of human skin explants presenting stretch marks, treated with TLE or vehicle control. Results: Skin roughness of stretch marks was significantly reduced in the TLE group after 8 weeks of treatment. Skin firmness of stretch marks was significantly increased in the TLE group after 4 weeks of treatment, and this improved effect was maintained until the end of the study. Dermal density and thickness were significantly increased in the TLE group compared to the placebo group. Furthermore, TLE restored the dermal condition of the stretch mark skin, up to normal skin levels. In addition, pro‐collagen I and elastin concentrations were found to be higher in the TLE‐treated stretch mark skin explants compared to the untreated ones, associated with higher quantities of TGF‐β production. Conclusion: These results revealed that TLE could help improve the aspect of stabilized stretch marks in women by restoring the matricial environment.